Parsonage-Turner syndrome presenting with left shoulder pain and weakness: a case report - Kulaklı, Fazıl; Duman, Sencer (The European Research Journal, 2020)
Parsonage-Turner syndrome is a clinical syndrome that begins with a sudden, neuropathic pain on the shoulder girdle, followed by pain loss over time. It is a rare syndrome that can be overlooked during differential diagnosis of shoulder pain and weakness. In this paper, we aimed to present a 39-year-old male patient with sudden onset left shoulder pain and weakness who were diagnosed with Parsonage-Turner syndrome.